PAPR Reduction in SC-FDMA by Pulse Shaping Using Parametric Linear Combination Pulses - AZURDIA-MEZA, Cesar A; LEE, Kyujin; LEE, Kyesan (IEEE communications letters, 2012)
A linear combination between two intersymbol interference (ISI) free parametric linear pulses was proposed in order to obtain a new family of Nyquist pulses. The new family of pulses is utilized for pulse shaping to reduce peak-to-average power ratio (PAPR). The proposed pulse contains a new design parameter, μ, giving an additional degree of freedom to minimize PAPR for a given roll-off factor, α, and transmission scheme. While keeping the same bandwidth, the frequency responses of the proposed pulses differ with different values of the parameter μ for a fixed roll-off factor. Simulations showed that PAPR reduction is achieved when compared to that of other existing filters for the interleaved subcarrier mode of single carrier frequency division multiple access (SC-FDMA).